Obowiązek posiadania dowodu osobistego i funkcje dowodów pod rządami dekretu z dnia 22 października 1951 roku o dowodach osobistych oraz w czasach współczesnych - Tomaszewska, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The fulfilment of basic civic duties has always entailed the need for individuals to bear certain responsibilities. Their weight varies depending on the content of the obligation itself and the political system of the state in which the obligation is fulfilled. Such a claim is fully justified if we consider the obligation to have an identity card, defined by the content of the Decree of 22 October 1951 and the Act of 6 August 2010 on Identity Cards. The analysis of the above-mentioned regulations allows for: emphasizing the obligation’s character as a basic civic duty, recalling the differences in the actual occurrence and social perception of ailments related to the implementation of the obligation to have an identity card in the times of the Polish People’s Republic and in the 21st century, while referring to the similarities and differences resulting from the visual aspects and functionality of contemporary and historical ID cards.
Keywords: dowody osobiste; obowiązek obywatelski; PRL; elektroniczny dowód osobisty; dekret o dowodach osobistych